Upaya Peningkatan Manajemen Pembalajaraan Kelas di Madasah Ibtidaiyah Ma’arif Sembego Maguwoharjo: Prospek dan Tantangan - Maemonah, Maemonah (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2016)
One of the development efforts the capabilities of educators with intensive assistance capability studies educators to learners, known as Action Research (PTK) in Government Elementary School (MI). From the guidance to teachers MI Diponegoro in the form of participatory research (PAR), there is an increasing understanding of the capabilities of teachers to various conditions learners well as the ability to innovate and improve the quality of learning undertaken by teachers towards their students on one side. On the other hand students also increased understanding in learning. The challenge, these efforts need to be done continuously so that it becomes a tradition in the process of structuring or management teacher learning in the classroom.